High‐Entropy Atomic Layers of Transition‐Metal Carbides (MXenes). Issue 39 (8th August 2021) - Du, Zhiguo; Wu, Cheng; Chen, Yuchuan; Cao, Zhenjiang; Hu, Riming; Zhang, Yongzheng; Gu, Jianan; Cui, Yanglansen; Chen, Hao; Shi, Yongzheng; Shang, Jiaxiang; Li, Bin; et al.
Abstract: High‐entropy materials (HEMs) have great potential for energy storage and conversion due to their diverse compositions, and unexpected physical and chemical features. However, high‐entropy atomic layers with fully exposed active sites are difficult to synthesize since their phases are easily segregated. Here, it is demonstrated that high‐entropy atomic layers of transition‐metal carbide (HE‐MXene) can be produced via the selective etching of novel high‐entropy MAX (also termed M n +1 AX n ( n  = 1, 2, 3), where M represents an early transition‐metal element, A is an element mainly from groups 13–16, and X stands for C and/or N) phase (HE‐MAX) (Ti1/5 V1/5 Zr1/5 Nb1/5 Ta1/5 )2 AlC, in which the five transition‐metal species are homogeneously dispersed into one MX slab due to their solid‐solution feature, giving rise to a stable transition‐metal carbide in the atomic layers owing to the high molar configurational entropy and correspondingly low Gibbs free energy. Additionally, the resultant high‐entropy MXene with distinct lattice distortions leads to high mechanical strain into the atomic layers. Moreover, the mechanical strain can efficiently guide the nucleation and uniform growth of dendrite‐free lithium on HE‐MXene, achieving a long cycling stability of up to 1200 h and good deep stripping–plating levels of up to 20 mAh cm −2 . Abstract : High‐entropy atomic layers of transition‐metal carbide (HE‐MXene) are produced via selectively etching a high‐entropy MAX phase, in which five transition‐metal species are homogeneously dispersed into one MX slab, giving rise to stable transition‐metal carbide in the atomic layers. The resultant HE‐MXene has distinct lattice distortions and strains, efficiently guiding the nucleation and uniform growth of lithium.